The Influence of The Anabolic Steroid Usage on The Physical Health: A Review - Chodkowski, Jakub; Grabowski, Filip; Rulewska, Natalia; Feruś, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction: Anabolic steroids are synthetic derivatives of testosterone commonly used to enhance athletic performance and physical appearance. Despite their popularity, their non-medical use is associated with significant health risks. This review aims to synthesize current knowledge on the impact of anabolic steroid use on physical health, emphasizing cardiovascular, hepatic, endocrine, and musculoskeletal systems, as well as broader systemic effects. Materials and Methods: A systematic literature review was conducted using peer-reviewed articles from databases such as PubMed, Scopus, and Google Scholar published between 2000 and 2023. Studies were selected based on relevance, with particular focus on human clinical trials, observational studies, and meta-analyses. Keywords included "anabolic steroids," "health effects," "cardiovascular risk," and "endocrine disruption." Results: Anabolic steroid use is linked to increased cardiovascular risks, liver dysfunction, endocrine disturbances, and musculoskeletal injuries. Key effects include hypertension, hepatotoxicity, testosterone suppression, infertility, and tendon injuries. Psychological impacts such as aggression and mood changes were also observed. Conclusions: Anabolic steroid use poses significant risks to multiple organ systems and overall health. Despite widespread awareness of these dangers, misuse persists, often driven by societal pressures and misinformation. Healthcare providers should prioritize prevention through education, early intervention, and support for individuals at risk. Future research should focus on long-term effects and effective strategies for harm reduction.